¿Qué lee la población estudiantil de Comunicación Colectiva de la Universidad de Costa Rica? - Rodríguez Álvarez, Juan Antonio (2015)
This article presents the reading habits of the students from the Collective Communication Sciences School from the University of Costa Rica. Moreover, it identifies the different habits by age and sex. This study is included in the results of the first Media Consumption Census held by this academic unit as part of the Pressing Educational Communication Research Project.